Pengaruh Aplikasi “Mommy Nifas” terhadap Peningkatan Pengetahuan dan Keterampilan Ibu - Nopi Anggista Putri; Dany Hilmanto; Zulvayanti Zulvayanti (Politeknik Kesehatan Tanjung Karang, 2021)
Complications of the puerperium are a contributing factor to the high maternal mortality rate (MMR). One effort to reduce the MMR is to increase the knowledge and skills of mothers regarding postpartum care. This study aims to analyze the effect of using an application that contains information about postpartum care to increase the knowledge and skills of mothers. This study uses a quasi-experimental design with a pre-posttest with a control group design. The subjects of the study were postpartum mothers in the work area of Gadingrejo Public Health Center from September to October 2019 with 60 respondents, consisting of 30 respondents from the treatment group and another 30 from the control group using consecutive sampling techniques. The intervention group is mothers who get the mommy nifas application and the control group is mothers who don't get application data analysis using the chi-square test. The results showed an increase in knowledge after giving higher mommy nifas application which is 71,5 (pre-test) to 93 (post-test) with a value of p-value<0,05. Skills improved from 50 (pre-test) to 70,5 (post-test) with a p-value<0,05. The percentage increase in knowledge after using the application is by 17% and skills by 40% with a value of p-value<0,05. The conclusion of this study is that there is an effect of increasing skills and increasing the percentage of mothers' knowledge after using mommy nifas applications.